Efektivitas Program Literasi dalam Meningkatkan Kemahiran Membaca Siswa SDN 002 Teluk Bintan - Cindy Indrawati; Dian Sari Simanullang; Evaliana Sarmauli Silalahi; Firna Putri Az Zahra; Novi Ramadhani; Tiofany Tiofany; Timoti Meilando; Voni Vonalia; Wan Solihin (Lembaga Pengembangan Kinerja Dosen, 2025)
Reading skills are basic skills that students must master, especially in 5th grade. A structured and consistent literacy program is very influential in improving reading skills. This article discusses the effectiveness of literacy programs with reading, discussion, and action activities implemented at SDN 002 Teluk Bintan. The success of literacy programs greatly depends on collaboration between teachers, principals, and adequate facilities. This collaboration creates an ecosystem conducive to fostering an interest in reading. This community service program implements a collaborative strategy involving discussion and active reading, a method that has been proven to effectively improve reading skills. The purpose of this study is to measure the improvement in students' reading skills after participating in the literacy program. The research method used is an experiment with a one-group pretest-posttest design involving 30 fifth-grade elementary school students. The instruments used are reading tests with themes of health, bullying, and social issues to collect data. Data analysis included a comparison of pretest and posttest scores using a t-test. The results showed a significant increase from a pretest average score of 71.6 (classified as fair) to a posttest average score of 86.5 (classified as good). The success of this program is supported by an interactive approach that emphasizes not only reading but also discussion and practical activities related to the material, thereby engaging students more cognitively and emotionally.These findings confirm that effective literacy programs improve reading skills and shape students' critical thinking skills, and can be recommended for literacy programs in other schools.